2004
DOI: 10.1007/s11255-004-6194-y
|View full text |Cite
|
Sign up to set email alerts
|

Potassium metabolism in patients with chronic kidney disease. Part II: Patients on dialysis (stage 5)

Abstract: Potassium is removed mainly by diffusion during dialysis. In hemodialysis, potassium removal averages 70-150 mmol per session, and the presence of glucose-free dialysate, sodium profiling, and hyperkalemia, may increase its removal. The most frequent potassium derangement in hemodialysis patients is hyperkalemia. Hemofiltration removes approximately 60 mmol of potassium per treatment. In peritoneal dialysis patients, despite lower potassium removal (about 30-40 mmol/day), hypokalemia is the most frequent elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…In this study, we observed changes in electrolytes and acid-base parameters similar to those changes described previously (24,26). However, we found no significant differences between patients with and without hemodialysis-induced LV systolic dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we observed changes in electrolytes and acid-base parameters similar to those changes described previously (24,26). However, we found no significant differences between patients with and without hemodialysis-induced LV systolic dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, although the degree of Kt/V did not influence serum potassium level during the study period in our study, inadequate haemodialysis in addition to poor dietary compliance could be still considered as the main cause of hyperkalaemia because the regulation of potassium homeostasis mainly depends on dialysis in ESRD patients on maintenance haemodialysis [17]. Besides high dietary potassium intake, there are other obvious factors to induce hyperkalaemia on stable patients on maintenance haemodialysis without ongoing hypercatabolic state, severe metabolic acidosis and reduction in the dialysis clearance are: (i) drugs used concomitantly that interfere potassium homeostasis, (ii) hypoaldosteronism and (iii) reduction in residual renal function [18]. But, in this study, those drugs such as b-blockers, diuretics, digoxin and NSAIDs did not affect serum potassium levels significantly during the 3-month study period.…”
Section: Discussionmentioning
confidence: 99%
“…If A-RRT is delayed, the ESKD patient may experience ‘rebound hyperkalemia' as the potassium ions return into the extracellular space but are not excreted by the kidneys [61]. Conversely, hypokalemia during RRT should be avoided because of the risk of cardiac arrhythmia and careful monitoring of potassium levels should be advocated [63]. The loss of ability to excrete a free-water load predisposes to the development of moderate-to-severe hypotonic hyponatremia.…”
Section: Ckd/eskd Patients Admitted In the Icumentioning
confidence: 99%